High-rate and ultralong cycle-life potassium ion batteries enabled by in situ engineering of yolk–shell FeS₂@C structure on graphene matrix - Zhao, Yi (2021)
The potassium-ion battery (PIB) represents a promising alternative to the lithium-ion battery for large-scale energy storage owing to the abundance and low cost of potassium. The lack of high performance anode materials is one of the bottlenecks for its success. The main challenge is the structural degradation caused by the huge volume expansion from insertion/extraction of potassium ions which are much larger than their lithium counterparts. Here, this challenge is tackled by in situ engineering of a yolk–shell FeS2@C structure on a graphene matrix. The yolk–shell structure provides interior void space for volume expansion and prevents the aggregation of FeS2. The conductive graphene matrix further enhances the charge transport within the composite. The PIB fabricated using this anode delivers high capacity, good rate capability (203 mA h g−1 at 10 A g−1), and remarkable long-term stability up to 1500 cycles at high rates. The performance is superior to most anode materials reported to date for PIBs. Further in-depth characterizations and density functional theory calculations reveal that the material displays reversible intercalation/deintercalation and conversion reactions during cycles, as well as the low diffusion energy barriers for the intercalation process. This work provides a new avenue to allow the proliferation of PIB anodes.